2015
DOI: 10.1136/emermed-2013-202551
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nosocomial pathogens in German ambulances: the SEKURE study

Abstract: In accordance with previous studies, disinfection and cleaning of areas with direct contact to patients or staff seem to be the most challenging. This should also be reflected in disinfection guidelines and the related continuing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 4 publications
1
32
0
3
Order By: Relevance
“…Based on prior EMS findings indicating hygienic challenges in relation to HTS [7, 15], we chose to sample the patient harness, the handle on the medic bag, the front of the defibrillator, the inside the blood pressure cuff, the handlebar in ambulance ceiling, and the wall next to the patient stretcher. To elucidate the level of microbial contamination on PRS, we sampled the torso and sleeve from the uniforms [11] and the upper side, and the palm of the dominating hand from the provider last in charge of a patient course [13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on prior EMS findings indicating hygienic challenges in relation to HTS [7, 15], we chose to sample the patient harness, the handle on the medic bag, the front of the defibrillator, the inside the blood pressure cuff, the handlebar in ambulance ceiling, and the wall next to the patient stretcher. To elucidate the level of microbial contamination on PRS, we sampled the torso and sleeve from the uniforms [11] and the upper side, and the palm of the dominating hand from the provider last in charge of a patient course [13].…”
Section: Methodsmentioning
confidence: 99%
“…Scarce information with little or no focus on infection status is given to the EMS providers before retrieval of the patient [6]. The ambulances are non-static environments that must be ready for service shortly after delivering the patient to the emergency department, hence offering limited time and equipment to clean and decontaminate [7]. In addition to logistic challenges, studies indicate that implementation of cleaning measures [7, 8] and efficiency of cleaning [9] within the EMS vary.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies showed significant MRSA colonisation3 and outlined the challenges EMS providers face when decontaminating ambulances 4. Wepler et al 5 showed that the frequency of German ambulances contaminated with MRSA was not related to the frequency of disinfection, and Rago et al 6 stress the importance of consciousness when designing disinfection protocols. Prior studies did not assess the colonisation of oxygen cylinders with MRSA in comparison with other sites within the ambulance.…”
Section: Introductionmentioning
confidence: 99%